The unheard victims: gender, policing and sexual violence - Javaid, Aliraza (Policing and society, 2020)
72,000 men in England and Wales are victims of sexual violence each year. While sexual violence against men is slowly becoming recognised as a sociological and criminological issue because victims are steadily coming forward due to changes in policy and practice, gradually improving the reporting rate that causes sociologists and criminologists to take notice of a necessity to address the issue, there still however remains a noticeable gap regarding the context, contours, and consequences of policing male rape within England. This paper makes some attempt to fill in this lacuna, using data including police officers who completed in-depth interviews and qualitative questionnaires (53 officers in total). This article focuses on several themes that emerged from the data, such as police insensitivity/secondary victimisation; police treatment of male rape; and police training, inter alia. It explores police officers’ level of comprehension relating to the topic of male rape and, in turn, evaluates police training (or lack thereof) provided to help with understanding male rape. It considers the implications of poor police practice with regards to male rape. The results show that there are some police discourses that suggest that only women can be victims of sexual violence, not men, shaping how some officers think about and respond to male rape victims in practice.